Levels of Tape Yeast in Corn Cob Bioconversion Affects Crude Protein Content and In Vitro Digestibility of Crude Fiber - Mullik, Marthen L.; Sabneno, Sabneno Yuliana; Yunus, Marthen; Dami Datto, Twen O. (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak; Vol 12 No 1 (2022): Pastura Vol. 12 No. 1 Tahun 2022DO - 10.24843/Pastura.2022.v12.i01.p07, 2022)
This study aimed to determine the effect of tape yeast levels on the content and in vitro digestibility of crude protein and crude fiber in the products of corn cob bioconversion. This completely randomized experimental design had five treatments and three replicates. The treatments were mixture of 2 kg copped corn cobs plus additive and addition of tape yeast at a level of 25 g (RT25), or 50 g (RT50), or 75 g (RT75), or 100 g (RT100), or 125 g (RT125). The results showed that crude protein content ranged from 10.16% to 11.74% and significantly affected by the levels of tape yeast. In contrast, total crude fibre content and in vitro digestibility of crude protein were not affected by tape yeast levels (P>0.05). Whereas, in vitro digestibility of crude fibre was significantly reduced from 26.35% to 22.78% when level of tape yeast was increased. It could be concluded that the use of tape yeast at a level 75 g per 2 kg chopped corn cobs is the best level in bioconversion because it has the highest protein content, and low crude fibre digestibility.   Keywords: protein, crude fibre, digestibility, tape yeast, corn cob